Application of 3D Laser Scanning Technology for Shield Tunnel Inspection. Issue 1 (January 2020) - Zhao, Hailin; Huang, Qiming; Wan, Shifu; Qi, Xingxin; Chen, Yunjian; Qiu, Wenge
Abstract: This paper describes the application of 3D laser scanning technology in shield tunnel inspection from the working mechanism. The point cloud data collection process, processing method and result analysis of the technology in shield tunnel inspection are introduced. Finally, combined with point cloud data obtained for dislocation and clearance inspection. The dislocation and clearance inspection are visually shown by the three - dimensional cloud chart. It shows that reliable inspection information can be obtained by using this technology, and has certain practical value for tunnel inspection.